Overosaurus paradasorum gen. et sp. nov. , a new sauropod dinosaur (Titanosauria: Lithostrotia) from the Late Cretaceous of Neuquén, Patagonia, Argentina - Coria, Rodolfo Anibal (2013)
A new lithostrotian sauropod, the small-sized Overosaurus paradasorum n. gen et sp. from the Anacleto Formation (Cam-panian, Late Cretaceous, Neuquén Group, Patagonia, Argentina) is here described. The specimen (MAU-Pv-CO-439) consists of a fully articulated vertebral series from the 10th cervical to the 20th caudal vertebra, the last cervical ribs, several dorsal ribs in articulation with their respective vertebrae, the complete right ilium and fragments of the left ilium. Overo-saurus paradasorum is diagnosed by a unique combination of characters that includes (1) posterior cervical vertebrae with long pre- and postzygapophyses that project beyond the anterior and posterior borders of the centrum, respectively, (2) postspinal lamina absent in all dorsal neural spines, (3) wide and massive 9th and 10th caudal centra that are slightly exca-vated laterally and have relatively flat ventral surfaces, (4) laminar projection on the posterior border of the second and third dorsal rib, (5) ilium proportionally shorter anteroposteriorly and taller dorsoventrally than in other lithostrotians, and (6) the preacetabular process of the ilium strongly deflected laterally and with a ventrolaterally tapering end. Analysis of the phylogenetic relationships of Overosaurus places it within the Aeolosaurini, as the sister taxon of a monophyletic group formed by Aeolosaurus rionegrinus, A. maximus, Gondwanatitan faustoi and Pitekunsaurus macayai. Overosaurus is a new representative of a highly diversified assemblage of Campanian lithostrotians from Patagonia that includes both Aeolosaurini and saltasaurids (e.g. Saltasaurus, Neuquensaurus)—this small new taxon falls within the low end of the size spectrum represented by these Late Cretaceous sauropods.